Chloroquine Psychosis: A Chemical Psychosis? - Mohan, D. (1981)
Psychotic states are mimicked by the use of many drugs including amphetamines, cannabis, lysergic acid diethylamide, psilocybin, mescaline, isoniazid, and L-dopa. A paranoid psychotic picture in a clear sensorium is characteristic of amphetamine psychosis. In developing countries, malaria among other diseases is a frequent indicator of chloroquine administration. The present communication reports a series of chloroquine-induced psychosis in a clear sensorium simulating affective illness, such as mania, mixed affective states, or depression. The psychosis disappeared after cessation of the drug, combined with or without the use of low dosage phenothiazines in excited patients. From our cases, two types of presentation of chloroquine psychosis could be seen: (1) psychic with clear sensorium, mood changes, alteration in motor activity, delusions, and hallucinations; and (2) psycho-organic with clouded sensorium, disorientation, and fleeting hallucinations. The precise nature of the mechanism of the psychosis is not clear because of the limited number of reported cases.